TRENDS OF INNOVATION DEVELOPMENT OF RUSSIA AND ITS STRATEGIC PRIORITIES - Vera G. Shiyko (Statistika i Èkonomika, 2016)
The article describes the main stages of innovation development of the Russian economy, analyzes the trends and the future of Russia’s strategic priorities. The focus is the need for the introduction of high technology, contributing to the creation of unique products and the occupation of new markets, the use of which leads to a new economic miracle - the rapid development of the industrial countries and their transformation into a post-industrial state. It is shown that the requirement of the time is the creation of a “new industrial economy” based on the production of high-tech innovative products based on high-tech industries, through the restoration of the reproductive process of the innovation cycle.